Peer-to-Peer modelling training on the FABLE-C in Addis-Adaba, Ethiopia - Chemarin, Charlotte; Mulatu, Kalkidan; Yonas, Getahah (2025)
The FABLE secretariat and Ethiopia’s FABLE team conducted a one-week in-person capacity sharing program in May 2025, in Addis Ababa, Ethiopia. Charlotte Chemarin, from the Alliance Bioversity-CIAT in Montpellier, France, member of the FABLE global secretariat, visited the Alliance Bioversity-CIAT office in Addis Ababa, Ethiopia, to lead a training and share her modelling experience with the Ethiopian country team.